Strategic Human Resource Quality Improvement For Non-Star Hotels In Lahat Regency: A Swot Analysis - Oneng Setya Harini; Vania Okky Putri; Mustika Permatasari; Mochammad Rian Ahdian Morena (CV Putra Publisher, 2026)
A company’s growth depends heavily on human resources with expertise of its staff; competent personnel. Therefore, having competent human resources in their respective fields is a must for any company. In Lahat Regency’s non-star hotels, the workforce is characterized by heavy multitasking, where employees often cover several departments due to limited staffing and specific occupancy levels. This study using a qualitative approach to identify methods, drivers, and barriers in human resource quality improvement, ultimately proposing strategic recommendations. Data were collected via in-depth interviews, observations, and documentation, then processed through a SWOT analysis of internal and external factors. Using SWOT-based analysis approach, this research contributes a strategic framework for quality enhancement. The findings suggest that improvement must move beyond basic staffing to include standardized service protocols across all non-star lodgings and rigorous performance evaluations based on guest feedback. Crucially, this study implies that for Lahat’s hospitality sector to remain competitive, management must prioritize coaching and digital promotion training. These results provide a practical roadmap for local operators and policymakers to synchronize regional tourism development with targeted human resource investment.